Effects of the Local Bone Renin-Angiotensin System on Titanium-Particle-Induced Periprosthetic Osteolysis - Zhao, Zhiping; Wang, Changyao; Xu, Yingxing; Wang, Xiangyu; Jia, Bin; Yu, Tengbo; Wang, Yingzhen; Zhang, Yongtao (Frontiers in Pharmacology, 2021)
Wear particles may induce osteoclast formation and osteoblast inhibition that lead to periprosthetic osteolysis (PPOL) and subsequent aseptic loosening, which is the primary reason for total joint arthroplasty failure. Local bone renin-angiotensin system (RAS) has been found to participate in the pathogenic process of various bone-related diseases via promoting bone resorption and inhibiting bone formation. However, it remains unclear whether and how local bone RAS participates in wear-particle-induced PPOL. In this study, we investigated the potential role of RAS in titanium (Ti) particle-induced osteolysis in vivo and osteoclast and osteoblast differentiation in vitro. We found that the expressions of AT1R, AT2R and ACE in the interface membrane from patients with PPOL and in calvarial tissues from a murine model of Ti-particle-induced osteolysis were up-regulated, but the increase of ACE in the calvarial tissues was abrogated by perindopril. Moreover, perindopril mitigated the Ti-particle-induced osteolysis in the murine model by suppressing bone resorption and increasing bone formation. We also observed in RAW264.7 macrophages that Ang II promoted but perindopril suppressed Ti-particle-induced osteoclastogenesis, osteoclast-mediated bone resorption and expression of osteoclast-related genes. Meanwhile, Ang II enhanced but perindopril repressed Ti-particle-induced suppression of osteogenic differentiation and expression of osteoblast-specific genes in mouse bone marrow mesenchymal stem cells (BMSCs). In addition, local bone RAS promoted Ti-particle-induced osteolysis by increasing bone resorption and decreasing bone formation through modulating the RANKL/RANK and Wnt/β-catenin pathways. Taken together, we suggest that inhibition of RAS may be a potential approach to the treatment of wear-particle-induced PPOL.